2019
DOI: 10.1016/j.bja.2019.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Novel neurosteroid hypnotic blocks T-type calcium channel-dependent rebound burst firing and suppresses long-term potentiation in the rat subiculum

Abstract: Background: Hypnotics and general anaesthetics impair memory by altering hippocampal synaptic plasticity. We recently reported on a neurosteroid analogue with potent hypnotic activity [(3b,5b,17b)-3-hydroxyandrostane-17carbonitrile; 3b-OH], which does not cause developmental neurotoxicity in rat pups. Here, we investigated the effects of 3b-OH on neuronal excitability in the subiculum, the major output structure of the hippocampal formation, and synaptic plasticity at two key hippocampal synapses in juvenile r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
2
9
1
Order By: Relevance
“…S2c and d ). These data confirm that, like in the subiculum of rat pups, 14 3β-OH inhibits T-currents but does not affect synaptic GABA A receptor currents in the CeM. In addition, we recorded picrotoxin-sensitive tonic GABA A current and found that alphaxalone potently enhanced it, whereas 3β-OH had no significant effect ( Fig 2 d).…”
Section: Resultssupporting
confidence: 85%
“…S2c and d ). These data confirm that, like in the subiculum of rat pups, 14 3β-OH inhibits T-currents but does not affect synaptic GABA A receptor currents in the CeM. In addition, we recorded picrotoxin-sensitive tonic GABA A current and found that alphaxalone potently enhanced it, whereas 3β-OH had no significant effect ( Fig 2 d).…”
Section: Resultssupporting
confidence: 85%
“… 32 , 33 Although 3β-OH is devoid of direct GABAergic activity in both thalamic 34 and hippocampal brain slices, 4 it produces an apparently similar EEG signature in rats. We have shown previously that 3β-OH may suppress neuronal excitability by inhibiting T-channel-dependent rebound bursting 5 and by decreasing presynaptic glutamatergic transmission. 4 Furthermore, 3β-OH may hyperpolarise thalamocortical neurones by inhibiting the baseline influx of Ca 2+ via T-type ‘window’ currents.…”
Section: Discussionmentioning
confidence: 91%
“…Based on loss of righting reflex data in juvenile rats, 5 we first examined the effects of a relatively low dose of 3β-OH (30 mg kg −1 , i.p.) on behaviour and cortical EEG activity in male and female rats.…”
Section: Resultsmentioning
confidence: 99%
“…Our investigations of novel general anaesthetics have focused on a class of agents referred to as the neuroactive steroids (neurosteroids). We recently published that the neurosteroid analogue (3b,5b,17b)-3-hydroxyandrostane-17-carbonitrile (3b-OH) blocks T-type calcium currents (T-currents) in the subiculum, 6 and is an effective hypnotic with a good safety profile when administered to rat pups. 7 The most currently used general anaesthetics are potent positive modulators of postsynaptic g-aminobutyric acid A (GABA A ) receptors and are invariably neurotoxic during the early stages of brain development in preclinical animal models.…”
mentioning
confidence: 99%